Early Detection of Nonalcholic Fatty Liver (NAFLD) on Ultrasound - Rizwan Ullah, Aqal Zaman, Arooba Khan, Moiz Inam Khan, Zeeshan Allah Rakha, Sheikh Atif Mehmood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nonalcoholic fatty liver abnormality is more typical determination in clinical practice and around the world. Obesity and diabetic individuals play a basic role in the development and improvement of this disease. Purpose: This study was done to detect and find out the frequency of nonalcoholic fatty liver abnormalities on ultrasound at Al Noor Ultrasound and KTH hospital Peshawar Pakistan. To review the information of NAFLD and also the hazardous factors for its advancement and the regions where future research is important. Methods: Cross sectional study was done and overall 230 patients were taken from ultrasound examination. Results: Total 230 patients were examined on Color Doppler Ultrasound and confirmed 150 diseased patients. In total patients the males are 54.34% and females are 45.65%. The most frequent disease in this study was nonalcoholic fatty liver and detected in 104 (69.33%) patients (75 males, 29 females) and although the remaining diseases frequencies were liver hydated cyst 12 (8%) patients, hepatitis 11 (7.33%) patients, liver cirrhosis 10 (6.66%) patients, hepatomegaly 8 (5.33%) and least frequent liver hematoma in 5 (3.33%) patients. Conclusion: The most frequent disease found in this study was nonalcoholic fatty liver. The key cause of this disease is the obesity and diabetic patients. Ultrasound is the modality of choice for early detection of nonalcoholic fatty liver disease.